Diagnosis of Internal Carotid Artery Stenosis Greater than 70% with Power Doppler Duplex Sonography - Koga, Masatoshi; Kimura, Kazumi; Minematsu, Kazuo; Yamaguchi, Takenori (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Duplex sonography is an effective tool for evaluating internal carotid artery (ICA) stenosis, and power Doppler imaging has improved its value in this regard. Our goal was to elucidate which parameters, such as linear stenosis, area stenosis, and peak systolic velocity (PSV), are the most reliable predictors of ICA stenosis greater than 70% using the method proposed by the North American Symptomatic Carotid Endarterectomy Trial (NASCET).METHODS: Duplex sonography with power Doppler imaging and cerebral angiography were performed prospectively in 75 patients (135 vessels). The grade of stenosis on angiograms was calculated by the NASCET method, and linear stenosis, area stenosis, and PSV were measured in the most stenotic part of the ICA.RESULTS: Angiography revealed 20 ICA vessels with stenosis greater than 70%. The correlation between angiographic stenosis and linear stenosis, area stenosis, and PSV was .82, .78, and .84, respectively. A sensitivity-specificity curve analysis determined optimal threshold values of linear stenosis, area stenosis, and PSV as predictors of ICA stenosis greater than 70% as 74.7%, 83.3%, and 200 cm/s, respectively. Calculations of positive and negative predictive values, and accuracy using the optimal threshold values were 90.5%, 99.1%, and 97.8% for linear stenosis; 76.0%, 99.1%, and 94.8% for area stenosis; and 100%, 100%, and 100% for PSV.CONCLUSION: All parameters corresponded relatively well with angiographic stenosis. In particular, PSV greater than 200 cm/s was the most reliable predictor of ICA stenosis greater than 70%. We believe that the combination of parameters plays a crucial role in the accurate assessment of ICA stenosis.